Fine particulate matter in the tropical environment: monsoonal effects, source apportionment, and health risk assessment - Khan, M. F.; Latif, M. T.; Saw, W. H.; Amil, N.; Nadzir, M. S. M.; Sahani, M.; Tahir, N. M.; Chung, J. X. (European Geosciences Union, 2016)
The health implications of PM2:5 in the tropical region of Southeast Asia (SEA) are significant as PM2:5 can pose serious health concerns. PM2:5 concentration and sources here are strongly influenced by changes in the monsoon regime from the south-west quadrant to the north-east quadrant in the region. In this work, PM2:5 samples were collected at a semi-urban area using a high-volume air sampler at different seasons on 24 h basis. Analysis of trace elements and water-soluble ions was performed using inductively coupled plasma mass spectroscopy (ICP-MS) and ion chromatography (IC), respectively. Apportionment analysis of PM2:5 was carried out using the United States Environmental Protection Agency (US EPA) positive matrix factorization (PMF) 5.0 and a mass closure model. We quantitatively characterized the health risks posed to human populations through the inhalation of selected heavy metals in PM2:5. 48% of the samples collected exceeded the World Health Organization (WHO) 24 h PM2:5 guideline but only 19% of the samples exceeded 24 h US EPA National Ambient Air Quality Standard (NAAQS). The PM2:5 concentration was slightly higher during the north-east monsoon compared to south-west monsoon. The main trace metals identified were As, Pb, Cd, Ni, Mn, V, and Cr while the main ions were SO2